Targeting improved patient outcomes using innovative product listing agreements: a survey of Canadian and international key opinion leaders - Thompson M; Henshall C; Garrison LP; Griffin AD; Coyle D; Long S; Khayat ZA; Anger DL; Yu R (Dove Medical Press, 2016)
Melissa Thompson,1 Chris Henshall,2 Louis P Garrison,3 Adrian D Griffin,4 Doug Coyle,2,5 Stephen Long,6 Zayna A Khayat,7 Dana L Anger,1 Rebecca Yu8 1Cornerstone Research Group Inc., Burlington, ON, Canada; 2Health Economics Research Group, Brunel University London, London UK; 3Pharmaceutical Outcomes Research and Policy Program, School of Pharmacy, University of Washington, Seattle, WA, USA; 4Government Affairs & Policy, Johnson & Johnson, High Wycombe, UK; 5School of Epidemiology, Public Health and Preventive Medicine, University of Ottawa, Ottawa, ON, Canada; 6Health and Life Sciences, Global Public Affairs, Calgary, AB, 7Health Systems Innovation at MaRS Discovery District, Toronto, ON, Canada; 8Strategic Health Technology Assessment, Government Affairs & Market Access, Janssen Inc., Toronto, ON, Canada Objectives: To address the uncertainty associated with procuring pharmaceutical products, product listing agreements (PLAs) are increasingly being used to support responsible funding decisions in Canada and elsewhere. These agreements typically involve financial-based rebating initiatives or, less frequently, outcome-based contracts. A qualitative survey was conducted to improve the understanding of outcome-based and more innovative PLAs (IPLAs) based on input from Canadian and international key opinion leaders in the areas of drug manufacturing and reimbursement. Methods: Results from a structured literature review were used to inform survey development. Potential participants were invited via email to partake in the survey, which was conducted over phone or in person. Responses were compiled anonymously for review and reporting. Results: Twenty-one individuals participated in the survey, including health technology assessment (HTA) key opinion leaders (38%), pharmaceutical industry chief executive officers/vice presidents (29%), ex-payers (19%), and current payers/drug plan managers/HTA (14%). The participants suggested that ~80%–95% of Canadian PLAs are financial-based rather than outcomes-based. They indicated that IPLAs offer important benefits to patients, payers, and manufacturers; however, several challenges limit their use (eg, administrative burden, lack of agreed-upon endpoint). They noted that IPLAs are useful in rapidly evolving therapeutic areas and those associated with high unmet need, a quantifiable endpoint, and/or robust data systems. The Canadian Agency for Drugs and Technologies in Health, the pan-Canadian Pharmaceutical Alliance, and other arms-length organizations could play important roles in identifying uncertainty and endpoints and brokering pan-Canadian PLAs. Industry should work collaboratively with payers to identify uncertainty and develop innovative mechanisms to address it. Conclusion: The survey results indicated that while challenging, use of IPLAs may be associated with various benefits. Collaboration among stakeholders remains key: Canadian agencies could play an important role in the success of these agreements, while industry should be proactive in offering solutions that will help improve outcomes across the entire health care system. Keywords: product listing agreement, survey, innovative, Canada, CADTH, pCPA